2018
DOI: 10.26773/mjssm.180908
|View full text |Cite
|
Sign up to set email alerts
|

Post-Match Changes in Muscle Damage Markers among U-21 Soccer Players

Abstract: Th is study aimed to investigate the eff ect of offi cial soccer matches on selected markers of muscle damage in U-21 soccer players. A group of 19 trained, healthy male soccer players from the junior category took part in this study. Blood samples were assessed pre-match and immediately aft er a match in response to a competitive (2×45 min) soccer match. Analysis was performed for muscle damage and infl ammatory markers. Signifi cant diff erences between two measures (before and aft er soccer match) exist in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
0
10
1
1
Order By: Relevance
“…Regarding LDH, although we observed an increase in the concentration in 24h and 48h, this increase was not significant, which differs from other results found in the literature 23,30 . However, as presented by Bessa, et al 31 , the magnitude of elevation of LDH is much lower in relation to CK; Thus, the intensity of training may not promote a significant difference in a football training session, which had not yet been observed in the literature.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding LDH, although we observed an increase in the concentration in 24h and 48h, this increase was not significant, which differs from other results found in the literature 23,30 . However, as presented by Bessa, et al 31 , the magnitude of elevation of LDH is much lower in relation to CK; Thus, the intensity of training may not promote a significant difference in a football training session, which had not yet been observed in the literature.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the proposed training session, composed of squats exercises followed a simulated football match can promote CK and DOMS elevation. It is known that a competitive football match is able to elevate CK and DOMS up to 48h after the match 1,8,23 . To the best of our knowledge, this is the first study to demonstrate that a routine training session can promote significant changes in skeletal muscle markers of damage in football players.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown a significant post-effort increase in the LDH activity, for example, after rugby and soccer matches [29,47,48] or short-term maximal exercise (Wingate test) [49]. The differences between the subgroups in this study in terms of the LDH activity might be the result of the poor adaptation of the goalie/substitute group, caused by the significant differences in the time spent on the pitch or the extent of physical effort during the match.…”
Section: Discussionmentioning
confidence: 99%
“…Performance decreases and energy demands increase [10]. By contrast, muscle-skeletal mass is an indicator of sports performance [11]. It contributes to the energy production during highintensity activities and provides absolute strength to athletes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Bjelica D, Masanovic B, Krivokapic D. Anthropometric measurements and body composition Balt J Health Phys Act. 2020;12(1):[11][12][13][14][15][16][17][18][19] …”
mentioning
confidence: 99%